The Use of Virtual Reality to Enhance Practical Skills in Health Education - Heru, Maulidiyah Junnatul Azizah; Dewi, Novela Eka Candra; Shandy, Putra Tri (International Journal of Instructional Technology, 2023)
This research focuses on the use of Virtual Reality (VR) as a tool to improve students' practical skills in health education. The study aims to evaluate the effectiveness of VR in developing both technical and non-technical skills among students and to identify VR's contribution to more sustainable and flexible learning. A qualitative approach with a case study method was used, involving in-depth interviews, participatory observation, and document analysis at Nurul Jadid University in East Java. The results showed that the use of VR significantly enhanced students' technical skills, such as accuracy and speed in performing medical procedures, as well as non-technical skills like communication, decision-making, and teamwork. Additionally, VR provided more flexible and sustainable access to practice sessions, overcoming the physical and logistical limitations typically faced in health education. The implications of this study suggest that VR has great potential to be integrated into the health education curriculum, offering innovative solutions to improve learning quality and better prepare students for careers in the medical field. The study also recommends further comprehensive research to accommodate various variables, such as gender and age, to provide a more targeted basis for policy.